Risk of intracranial meningioma in patients with acromegaly: a systematic review - Guo, Amy X.; Job, Asha; Pacione, Donato; Agrawal, Nidhi (Frontiers in Endocrinology, 2024)
Acromegaly is a rare endocrine disorder caused by hypersecretion of growth hormone (GH) from a pituitary adenoma. Elevated GH levels stimulate excess production of insulin-like growth factor 1 (IGF-1) which leads to the insidious onset of clinical manifestations (1). The most common primary central nervous system (CNS) tumors, meningiomas originate from the arachnoid layer of the meninges and are typically benign and slow-growing. Meningiomas are over twice as common in women as in men, with age-adjusted incidence (per 100,000 individuals) of 10.66 and 4.75, respectively (2). Several reports describe co-occurrence of meningiomas and acromegaly (3). We aimed to determine whether patients with acromegaly are at elevated risk for meningioma. Investigation of the literature showed that co-occurrence of a pituitary adenoma and a meningioma is a rare phenomenon, and the majority of cases involve GH-secreting adenomas. To the best of our knowledge, a systematic review examining the association between meningiomas and elevated GH levels (due to GH-secreting adenomas in acromegaly or exposure to exogenous GH) has never been conducted. The nature of the observed coexistence between acromegaly and meningioma -whether it reflects causation or mere co-association -is unclear, as is the pathophysiologic etiology.